Digital Technologies in the Education and the BNCC: proposal of a Student-Cyborg-Hacker (Olhar de Professor, 2022)
This paper has the purpose to analyze the impact of neoliberal discursive practices within the BNCC (Curricular Common National Basis) and the “ideal type” of the student/worker-entrepreneur in the Digital Culture. The methodological and theoretical approach leading this discussion is based on the perspective of the qualitative method and the bibliographic research in terms of the process. We will defend another possibilities of educative uses of Digital Technologies of Information and Communication that goes beyond technical purposes, presenting our against hegemonic conception of the Cyborgue-Hacker-Student.
Keywords: Digital Culture. BNCC. Neoliberalism. Cyborgue-Hacker-Student.